Contested Bodies of Childhood and Youth
XVII, 260 p. 9 illus.
Keywords: Demonstrating the contested and differentiated nature of childhood and youth embodiment, this book responds to political and media discourses that stigmatise 'unruly' youthful bodies, by combining the critical analysis of imagined and disciplined youthful bodies with a focus on young people's lived and performed, embodied subjectivities.